2010
DOI: 10.1186/1743-422x-7-105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of wild-type measles viruses isolated in China, 2006-2007

Abstract: Molecular characterization of wild-type measles viruses in China during 1995-2004 demonstrated that genotype H1 was endemic and widely distributed throughout the country. H1-associated cases and outbreaks caused a resurgence of measles beginning in 2005. A total of 210,094 measles cases and 101 deaths were reported by National Notifiable Diseases Reporting System (NNDRS) and Chinese Measles Laboratory Network (LabNet) from 2006 to 2007, and the incidences of measles were 6.8/100,000 population and 7.2/100,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
(18 reference statements)
4
27
0
Order By: Relevance
“…This is consistent with recently published data from China [20]. In addition, we identified genetic variations in both the N and H genes of the wild-type MV isolates obtained from this outbreak and demonstrated diminished neutralizing antibody titers when post-vaccination sera were tested against the wild-type strains.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with recently published data from China [20]. In addition, we identified genetic variations in both the N and H genes of the wild-type MV isolates obtained from this outbreak and demonstrated diminished neutralizing antibody titers when post-vaccination sera were tested against the wild-type strains.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the incidence rate in Jilin Province rose to 17.41/ 100,000 in 2006 [26]. It has been proposed that increased migration (floating population) and decreased vaccination may be responsible for the recent upswing in measles cases throughout China [20]. The preponderance of measles cases in susceptible individuals in the present report would support this.…”
Section: Discussionsupporting
confidence: 83%
“…Phylogenetic analyses conducted during the early part of the last decade identified two clusters (cluster 1 and 2) within the Chinese genotype H1 . Previously, importation of genotype H1 viruses into Taiwan, Hong Kong, and Europe, for which 100% sequence homology was shown with genotype H1 viruses which were circulating in mainland China [Ji et al, 2010]. This is in line with the present study in which phylogenetic analysis showed that the Iranian H1 strains were members of Cluster 1.…”
Section: Discussionsupporting
confidence: 90%
“…Measles and rubella are similar diseases, both characterized by a rash that may be difficult to differentiate clinically (35). In addition, rubella epidemics usually occur in the spring or early summer, similar to measles, peaking between April and May (13). Therefore, during the measles elimination campaign in China, particularly in 2009, when the incidence of rubella was higher than that of measles, measles control might have been hampered because large numbers of suspected measles cases, which were in reality rubella cases, may have appeared.…”
Section: Discussionmentioning
confidence: 99%